Stator tooth shape optimization for double salient hybrid excitation generator based on asymmetric circuit analysis. Issue 6 (24th October 2019) - Yao, Shuchun; Zhang, Wei
Abstract : Purpose: This paper aims to clarify the relationship between stator tooth shape and DC voltage fluctuation of a double salient hybrid excitation generator (DSHEG). It analyzes the asymmetrical characteristics of the magnetic circuit and inductance between each phase. The study aims to reduce voltage fluctuation by using a stator shape optimization scheme, which helps reducing inductance difference. Design/methodology/approach: This paper opted for a method combined with theoretical analysis, simulation and experimental verification. The stator tooth optimization scheme is given based on theoretical asymmetrical analysis and Taguchi method. A series of two-dimensional finite element analysis simulation of different conditions are conducted. Two prototypes with different stator tooth shape are made and experiments are carried out. Findings: The paper provides empirical insights into how the stator tooth shape influences the asymmetry of inductance and DC voltage fluctuation. Compensation adjustments to the stator tooth shape can narrow the inductance differences of each phase. It suggests that "LTL" shaped DSHEG has lower voltage ripple than "III" shaped DSHEG without sacrificing output power. Research limitations/implications: Because of the chosen research approach, the gap between magnets and stator and end effect are not considered. Errors exist between simulation and experimental results. Practical implications: The paper includes implications for other "C" shaped tooth optimization. Study on phase asymmetry of the special machine can further improve quality testing and simplify control strategy. Originality/value: This paper analyzes the asymmetry of DSHEG and proposes an optimized stator tooth shape to reduce DC voltage fluctuation.